Pengaruh Konsentrasi NaOH terhadap Sifat Termal Komposit Eceng Gondok dan Carbon Nanotube (CNT) dalam Matriks HDPE - Anggrainy, Rani; Riza Wirawan; Siska Titik Dwiyati (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
This study aims to determine the effect of alkali concentration on the thermal properties of HDPE composites with water hyacinth and carbon nanotubes (CNTs). The method used in this study is the experimental method. Composites made of natural fiber filler, the alkali treated water hyacinth. The water hyacinth was also filled was treated in alkali solution at various concentration (0%, 2%, 4%, 6%, and 8%). In addition to using water hyacinth fiber, the carbon nanotube (CNT) in a matrix of high-density polyethylene (HDPE). The composites were made using Rheomix OS machine. Furthermore, thermal testing of composite specimens using machine Thermogravimetric Analysis (TGA) were conducted. The results obtained from testing the thermal properties is the thermal resistance value. Thermal resistance of composites with alkali treatment of 0%, 2%, 4%, 6%, and 8% were 258,9 0C, 259,5 0C, 260,3 0C, 264,0 0C, and 265,9 0C, respectly. Based on these results it can be concluded that the concentration of NaOH improves the thermal resistance of the composite.